A CORRELATIONAL STUDY ON SENIOR HIGH SCHOOL STUDENTS’ STUDY HABITS AND THEIR ENGLISH ACHIEVEMENT - Randa, Gusti Muhammad; Supardi, Iwan; Ikhsanudin, Ikhsanudin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aimed to find out the correlation between study habits and the English achievement of the tenth grade students at SMA N 03 Ketapang in the academic year of 2017-2018. Students’ sex was considered as another predictor variable. Wrenn (1941) Study Habits Inventory (SHI) was used to measure the students’ study habits. Students’ score from the English test was considered as the students’ English achievement. Pearson product-moment found that there was a positive correlation between students study habits and the English achievement with a strong level of correlation. Which meant as the level of study habits increases, the English achievement also increases. The female group had a higher correlation than the male. From the four aspects of the study habits, General habits and Attitudes of Works (GH and AW) contributed the most for the English achievement of the female students. Distribution of Time and Social Relationship of Study (DT and SR) gave the biggest contribution for the English achievement of the male students. This study implied the male students should contribute more time for study out of the school’s hours, and the female students should use more strategies in learning English. Keywords: Correlational study, study habits, English achievement, sex